A Conceptual Frame Using 'Knowledge' As a Lens for Deconstructing the Sendai Framework Priority 1: Understanding Disaster Risks. (2018) - Toinpre, O.; Gajendran, T.; Mackee, J.
Abstract: Following increases in the frequency and magnitude of disasters over the past decades, continuous knowledge production and dissemination has become a crucial pathway for understanding disaster risks. The Sendai Framework provides guidance for various levels of governance and well lays emphasis on managing 'disaster risks'. While a great deal of existing scholarship has contributed immensely to proactive participation of key players in the public and private sectors, the interpretation of knowledge produced by academia and professional organizations that aids in better understanding for ease of planning and implementation becomes a challenging and rigorous task. The aim of this paper is to present a conceptual framework that simplifies the interpretation of 'knowledge creation' and 'knowledge dissemination' connecting the Sendai priority one focus and requisite actions for disaster risk reduction at local, national, global and regional levels. The intended outcome is to better enhance understanding using 'knowledge' as a lens for key players and stakeholders involved in disaster risk reduction activities. This is achieved through the review of the role of knowledge and knowledge management literature for understanding disaster risks and utilizes an exploratory approach to further create a theoretical linkage with the focus of the Sendai Framework. The paper suggests that appropriate and continuous interpretation of knowledge created and disseminated has the propensity to stimulate and assist in achieving improved disaster risk reduction outcomes and judicious harnessing of resources required for achieving such tasks. The limitation of this paper is that it utilizes a knowledge lens to achieve its aim while acknowledging that other lenses can be used to provide better understanding and clarity of the subject matter.